Influence of Epidemiological Risk Factors for Occurrence of Hepatitis B Virus (HBV) Co-Infection in HIV/AIDS Patients: (Study in dr. Kariadi Hospital, Semarang, Indonesia) - Narcisse Musafili; Suharyo Hadisaputro; Muchlis Achsan Udji Sofro; Dwi Sutiningsih (Master of Epidemiology, School of Postgraduate Studies, Diponegoro University, Indonesia, 2022)
Background: Chronic hepatitis, liver cirrhosis, and hepatocellular carcinoma are all have a major cause which is Hepatitis B virus (HBV). Given the fact that HIV and HBV are all transmitted through the same routes, co-infection is common. The objective of this research is to identify several risk factors which influence the occurrence of Hepatitis B virus infection in HIV/AIDS patients at Kariadi, Semarang, Indonesia. Method: This research is analytical observational with a case control study design, a sample of 68(34 cases and 34 controls) For all HIV patients involved in the study, samples were determined by a positive HBsAg test, The dependent variable is HBV occurrence in HIV/AIDS individuals and dependent variable were CD4≤100, Age>30,gender,marital status ,level of education ,male who have sex with other male(MSM),Analysis of data was done through univariate, bivariate and multivariate analysis with logistic regression.Result: Variables that were proven to influence the occurrence HBV infection in HIV/AIDS individuals, after analysis were CD4≤100(p= 0.003 OR=7.535, 95% CI=(2.029-27.990 ) , being male who do sex with male( MSM) (P=0.027 ,OR=3.544 ,95%CI=( 1.158-10.848) . The probability for HIV/AIDS patients to be infected by HBVirus when they have both these risk factors is equal to 88.18%.Conclusion: The factors that were proven to affect the influence of occurrence Hepatitis B virus in HIV/AIDS patients were, CD4≤100 and being male who do sex with other male (MSM).